COCOA MARKETING CHANNEL ANALYSIS IN MARGOLEMBO VILLAGE, MANGKUTANA DISTRICT, EAST LUWU REGENCY - Heliawaty, Heliawaty; Rukmana, Didi; Khotimah, IIn Wulan (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The cocoa marketing problem faced is the lack of information on marketing channels for farmers whereas from the farmer's point of view as producers, information regarding effective and efficient marketing channels is one of the things that can encourage increased cocoa production. The importance of access to marketing information for farmers so that farmers can find out directly the selling price of cocoa from each marketing agency. The purpose of this research is to analyze the size of the margin in each cocoa bean marketing channel that has been formed. The analysis in this study includes channel analysis and marketing functions, marketing margins and efficiency. The results showed that there were 2 marketing channels in Margolembo Village, where channel I: farmers --- wholesalers --- cocoa management companies and channel II: farmers --- collecting traders --- wholesalers --- cocoa management companies. Marketing functions carried out by cocoa bean marketing institutions include exchange functions, physical functions and facility functions. The biggest margin, cost and profit value is in channel II, which is Rp 4,000. Based on the marketing efficiency analysis obtained, the two marketing channels in Margolembo Village are efficient and channel I is the most efficient marketing channel with a value of 4.4% and marketing channel II with an efficiency value of 6.9%. The conclusion of this research is that marketing channel I's marketing margin is Rp 1,000/kg and in marketing channel II is Rp 4,000/kg.